Assessment of the suitability of limestone aggregate in Sarawak as coarse aggregate in concrete - Chin Hon Sin; Yeo Jerome Song; Mo Kim Hung; Yuen Choon Wah; Morris Cassidy (MATEC Web of Conferences, 2025)
This study investigates the suitability of limestone aggregate sourced from the Sta’at quarry in Lundu, Sarawak, as a substitute for granite aggregate in concrete. The physical and mechanical properties of limestone and granite aggregates, along with their performance in concrete were evaluated following international and local standards. Both aggregates demonstrated compliance with key requirements, including acceptable fines content, bulk density, water absorption, and durability against fragmentation and chemical attack. Limestone had slightly higher elongation but comparable density and water absorption to granite. Mechanical properties such as aggregate crushing value and impact value indicated adequate strength for construction use. Concrete made with limestone aggregate exhibited better workability, with a higher slump than granite concrete, while maintaining similar hardened density. Although granite- containing concrete had slightly higher compressive strength, limestone concrete could exhibit similar flexural and tensile strengths. Durability assessments showed that limestone concrete had lower water penetration and chloride ion permeability. These findings suggest that the investigated limestone aggregate can serve as a viable alternative to granite in concrete applications, ensuring structural integrity and durability while supporting sustainable material diversification in construction. This can contribute to the efficient utilization of locally available materials.